EVERYDAY LIFE AT WAR: THE PERUVIAN COMBATANT IN THE MOUNTAINS DURING THE BREÑA CAMPAIGN (1881-1883) - López Chang, Aramis (2024)
This investigation focuses on reconstructing the daily life of Peruvian troops during the Breña Campaign, a period of the Pacific War in which Peruvian forces led by General Andrés Avelino Cáceres faced three Chilean military expeditions in the mountains between April 1881 and July 1883. Unlike most studies that mainly address the political-military aspects of the campaign, this article places emphasis on the subjectivity of the actors involved, exploring their experiences, sensitivities and emotions through of testimonial records. Use as a methodology sources such as letters, memoirs, campaign diaries, communications from war correspondents, official documents and observations of foreign travelers, the study examines how soldiers and other actors perceived and described their survival strategies, food, environment, the enemy, violence and the ties between comrades. The article concludes that this campaign was the longest and most difficult of the entire Pacific War, due to the extreme living conditions and the unconventional nature of the war in geographically challenging and hostile terrain for both Peruvian and Chilean forces.